2017
DOI: 10.1080/15548627.2017.1320636
|View full text |Cite
|
Sign up to set email alerts
|

IL17A augments autophagy in Mycobacterium tuberculosis-infected monocytes from patients with active tuberculosis in association with the severity of the disease

Abstract: During mycobacterial infection, macroautophagy/autophagy, a process modulated by cytokines, is essential for mounting successful host responses. Autophagy collaborates with human immune responses against Mycobacterium tuberculosis (Mt) in association with specific IFNG secreted against the pathogen. However, IFNG alone is not sufficient to the complete bacterial eradication, and other cytokines might be required. Actually, induction of Th1 and Th17 immune responses are required for protection against Mt. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 70 publications
3
35
0
Order By: Relevance
“…Among them, IL-17A and IL-17F share a similar structure and have similar roles in the immune response against Mtb infection. 10,11 The roles of other members of the IL-17 family are currently not known in Mtb infection.…”
Section: Th17-related Cytokines/th17-like Cells and Their Roles In Mtmentioning
confidence: 99%
“…Among them, IL-17A and IL-17F share a similar structure and have similar roles in the immune response against Mtb infection. 10,11 The roles of other members of the IL-17 family are currently not known in Mtb infection.…”
Section: Th17-related Cytokines/th17-like Cells and Their Roles In Mtmentioning
confidence: 99%
“…Protection against necrosis (by preventing damage to the internal mitochondrial membrane 5 and promoting rapid repair of the plasma membrane 7 ) and the switch towards programmed cell death by apoptosis are key mechanisms in the resolution of the infection. We and other authors have demonstrated that activation of autophagy can result in the elimination of the bacteria in autolysosomes 14,29,30 . Furthermore, autophagy also controls inflammation by regulating signaling pathways of the innate immunity, removing endogenous agonists from the inflammasome and by modulating the secretion of immune mediators.…”
Section: Discussionmentioning
confidence: 85%
“…First, we performed a kinetic study in which the autophagy levels in stimulated-cells from HD and TB patients were evaluated by flow cytometry as described before 14 . As shown in Figure 5A and B, a significant increase in the percentage of CD14 + LC3A, B-II + monocytes and in the relative mean fluorescence intensity (rMFI) was detected in cells treated with PGE2 for 16 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intermediate CD14+CD16+ monocytes can promote microbial resilience, classical CD14+CD16-monocytes inhibit the intracellular growth of M. tuberculosis [20]. Moreover, interleukin 17A and vitamin D3 have been reported to enhance the autophagic action of monocytes against M. tuberculosis infection in vitro [21,22]. However, very few studies have determined the various stages of the activation or inhibition of circulating monocytes in tuberculosis patients.…”
Section: Introductionmentioning
confidence: 99%